A Study of the Emotional Intelligence and Personality Traits of University Finance Students - Ana M. Rosales-Pérez; Manuel A. Fernández-Gámez; Macarena Torroba-Díaz; Jesús Molina-Gómez (MDPI AG, 2021)
Studies on financial behavior indicate that emotional intelligence (EI) and personality traits (PTs) explain much of the bias in financial activity. This study aims to identify in which dimensions of theEI and PTs of university students in finance further training is needed to avoid financial behavior bias. To this end, the EI and PT levels of a sample of university finance students and financial industry professionals were compared using the Trait Emotional Intelligence Questionnaire (TEIQue) and Big Five Inventory questionnaire. Subsequently, the dimensions of EI and PTs in which students have a deficit compared to professionals were identified, and the impacts that this deficit causes on the financial behavior of students were determined. The results indicate that students are deficient in the EI competencies related to empathy, emotion regulation, self-motivation, stress management, optimism, and self-esteem. Furthermore, PTs are related to kindness, awareness, openness, and extraversion. This deficit makes students more likely to have financial behavior biases such as risk tolerance, endowment, optimism, self-control, and loss aversion. These findings suggest that universities should be aware of providing financial students with full training in EI and PTs to help them successfully address their professional future.